Transition-metal-catalyzed hydrogen-transfer annulations: access to heterocyclic scaffolds - Nandakumar, Avanashiappan; Midya, Siba Prasad; Landge, Vinod Gokulkrishna; Balaraman, Ekambaram (Angewandte Chemie-International Edition, 2015)
The ability of hydrogen-transfer transition-metal catalysts, which enable increasingly rapid access to important structural scaffolds from simple starting materials, has led to a plethora of research efforts on the construction of heterocyclic scaffolds. Transition-metal-catalyzed hydrogen-transfer annulations are environmentally benign and highly atom-economical as they release of water and hydrogen as by-product and utilize renewable feedstock alcohols as starting materials. Recent advances in this field with respect to the annulations of alcohols with various nucleophilic partners, thus leading to the formation of heterocyclic scaffolds, are highlighted herein.